Comparative Genomic Analysis of Seven Vibrio alginolyticus Strains Isolated From Shrimp Larviculture Water With Emphasis on Chitin Utilization - Xue, Ming; Huang, Xuemin; Xue, Jiawei; He, Runduan; Liang, Guojian; Liang, Huafang; Liu, Jianyong; Wen, Chongqing (Frontiers in Microbiology, 2022)
The opportunistic pathogen Vibrio alginolyticus is gaining attention because of its disease-causing risks to aquatic animals and humans. In this study, seven Vibrio strains isolated from different shrimp hatcheries in Southeast China were subjected to genome sequencing and subsequent comparative analysis to explore their intricate relationships with shrimp aquaculture. The seven isolates had an average nucleotide identity of ≥ 98.3% with other known V. alginolyticus strains. The species V. alginolyticus had an open pan-genome, with the addition of ≥ 161 novel genes following each new genome for seven isolates and 14 publicly available V. alginolyticus strains. The percentages of core genes of the seven strains were up to 83.1–87.5%, indicating highly conserved functions, such as chitin utilization. Further, a total of 14 core genes involved in the chitin degradation pathway were detected on the seven genomes with a single copy, 12 of which had undergone significant purifying selection (dN/dS < 1). Moreover, the seven strains could utilize chitin as the sole carbon-nitrogen source. In contrast, mobile genetic elements (MGEs) were identified in seven strains, including plasmids, prophages, and genomic islands, which mainly encoded accessory genes annotated as hypothetical proteins. The infection experiment showed that four of the seven strains might be pathogenic because the survival rates of Litopenaeus vannamei postlarvae were significantly reduced (P < 0.05) when compared to the control. However, no obvious correlation was noted between the number of putative virulence factors and toxic effects of the seven strains. Collectively, the persistence of V. alginolyticus in various aquatic environments may be attributed to its high genomic plasticity via the acquisition of novel genes by various MGEs. In view of the strong capability of chitin utilization by diverse vibrios, the timely removal of massive chitin-rich materials thoroughly in shrimp culture systems may be a key strategy to inhibit proliferation of vibrios and subsequent infection of shrimp. In addition, transcontinental transfer of potentially pathogenic V. alginolyticus strains should receive great attention to avoid vibriosis.